Much native data, little longitudinal information: a model of information for the continuity of care, from prenatal assistance to the emergency in maternities - TVQ, Sá; RALP, Aguiar; ZSN, Reis (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2021: Anais do XXI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2021.16059, 2021)
Obstetric caring demands a continuous process of information sharing between health professionals. However, the lack of communication between points of assistance has allowed for an accumulation of local data without the benefits of data interoperability. The study’s objective is to develop an information model with essential obstetric data to foster the continuity of information. An exploratory research involved discussions of fictitious cases of obstetric emergencies and ninety electronic medical records (EMR) were used to validate the model. The minimum antenatal dataset entries was structured into nine sections, and fifty-six data entries. The development of an information model, based on the standard of interoperability, has the potential to overcome the informality of EMR.